Carpal Tunnel Syndrome comparison of open surgical versus endoscopic treatment - جابر, علي; علي يوسف,; عزة المحمد , (Latakia University Journal -Medical Sciences Series, 2022)
Objective: The aim of this study is to evaluate the functional outcome of the different surgical treatments of Carpal Tunnel Syndrome . In addition to, detection complications resulting from the surgery. Patients and Methods: Retrospective comparative study conducted for the period six Monthes (May 2019 – 0ct 2019) at Tishreen University Hospital in Lattakia-Syria. The study included two groups of patients were compared: group1 consisted of 17 patients (56.6%)who underwent regular open incision, mid- palmer mini incision in carpal tunnel release, whereas group 2 consisted of 13 patients (43.4%) who underwent endoscopic technique in carpal tunnel release . Results: The median age was 50 years, the most frequent age group was 46-60 year (43%), followed by the group 20-45 year ( 30 %). females represented 86.5 % of the patients, and right Hand alone was affected in 20 patients (66.6%), left Hand alone was affected in 7 patients (23.4%) and 3 patients (10%) with bilateral carpal tunnel syndrome whom underwent surgical release with both techniques. The Boston questionnaire was administered preoperatively and postoperatively to the Patients, and their functional capacities and symptom severities were recorded preoperatively and in the postoperative sixth month. Demographic data and preoperative Boston symptomatic and graphic data and functional scores were similar between both groups. Asignificant improvement was obtained in the Boston symptomatic and functional scores of both groups with no significant different between groups at any evaluation, except Pain scores and Patients satisfaction were better within the erst three months postoperative in group 2, although Pain scores and patients satisfaction were not significantly different at the end of the study . Conclusion: Both techniques are well tolerated with better results in terms of time to return to work in endoscopic patients.